Exploration of Phenolic Compound from The Stem Bark of Garcinia latissima Miq. - Retno Purbowati; Taslim Ersam (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), ITS, 2019)
Genus Garcinia, which well known as mangosteen family. It is belonging Cluciaceae family, consists of over 100 species. It is widely distributed in Southeast Asia. There are 77 species of this genus grows throughout Indonesia. Genus Garcinia have been identified to be a rich source of phenolic compounds, including xanthones, biflavonoids, benzophenones, depsidones, and triterpenoids. Some of those have been reported to have several biological activities, such as antioxidant, antidiabetic, and anticancer. Garcinia latissima Miq. is an endemic plant growing in Indonesia, especially in Papua Island, and its neighbouring country, Papua New Guinea. It is called Dolomagata by local people in Maluku. The plant usually grows with the straight and cylindrical stem. It has short buttresses and it has 50-80 cm diameter. Previous reports have revealed antimicrobial and antioxidant activites of the leaves, fruits, and stem bark extracts of the plant. Phytochemical investigation of the stem bark of G. latissima Miq. led to the isolation of new pyranoxanthones, latisxanthones-A-D. In this work, the isolation and structural elucidation of secondary metabolites from the stem bark of G. latissima Miq. will be conducted. Three known compounds such as kaempferol (1,2), 1,3,6,7-Tetrahydroxy-2-(3-methyl-but-2-enyl)-xanthen-9-one (3), 1,3,7 trihydroxy xanthone (4) were isolated from the ethyl acetat fraction.